-3(-6w+5)-3w=3(w-3)-9

Simple and best practice solution for -3(-6w+5)-3w=3(w-3)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-6w+5)-3w=3(w-3)-9 equation:



-3(-6w+5)-3w=3(w-3)-9
We move all terms to the left:
-3(-6w+5)-3w-(3(w-3)-9)=0
We add all the numbers together, and all the variables
-3w-3(-6w+5)-(3(w-3)-9)=0
We multiply parentheses
-3w+18w-(3(w-3)-9)-15=0
We calculate terms in parentheses: -(3(w-3)-9), so:
3(w-3)-9
We multiply parentheses
3w-9-9
We add all the numbers together, and all the variables
3w-18
Back to the equation:
-(3w-18)
We add all the numbers together, and all the variables
15w-(3w-18)-15=0
We get rid of parentheses
15w-3w+18-15=0
We add all the numbers together, and all the variables
12w+3=0
We move all terms containing w to the left, all other terms to the right
12w=-3
w=-3/12
w=-1/4

See similar equations:

| 3–4d=-5 | | 2-2(1+8x)=8x+7(-4-4x) | | 12x+20=4x/3 | | 4x-25=-3 | | 11−2f=5 | | x^2+11x-64=90 | | 200000=(20*0.6x)+(24*0.4x)-6280000 | | -6p-8(4p+)=98 | | 8p+2P=60 | | -7u-9+2(3u+7)=-2(u+2) | | 30x^2=15x | | 2-2(1+8x=8x+7(-4-4x) | | -7-9+6u+14=-2u+4 | | x+76+43=180 | | 5+3q=6+2q= | | -3=c-7c= | | 7(6g+3)+40=126 | | 7x-+4=24 | | x2-21x=-110 | | 20-2k=2 | | 2-2k=-4 | | 4f-28=100 | | x+90+53=180 | | -3.5x=54.60 | | 27+0.10x=23+0.15x | | 5z-10=-15 | | 25x=156 | | 24=9x+4-5x= | | 2x=5.9 | | 7(2n-8)=8+5(n-2) | | 3(x-2)+20=-4 | | 3q-3=-9 |

Equations solver categories